2013
DOI: 10.1161/jaha.112.000018
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Increases Early Atherosclerosis and Promotes Plaque Inflammation Through a Placental Growth Factor‐Dependent Mechanism

Abstract: BackgroundAldosterone levels correlate with the incidence of myocardial infarction and mortality in cardiovascular patients. Aldosterone promotes atherosclerosis in animal models, but the mechanisms are poorly understood.Methods and ResultsAldosterone was infused to achieve pathologically relevant levels that did not increase blood pressure in the atherosclerosis‐prone apolipoprotein E–knockout mouse (ApoE−/−). Aldosterone increased atherosclerosis in the aortic root 1.8±0.1‐fold after 4 weeks and in the aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 69 publications
(115 reference statements)
3
90
0
3
Order By: Relevance
“…2013) and atherosclerosis (McGraw et al. 2013). We have previously reported that MR activation by aldosterone upregulates ICAM‐1 in human coronary ECs (Caprio et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2013) and atherosclerosis (McGraw et al. 2013). We have previously reported that MR activation by aldosterone upregulates ICAM‐1 in human coronary ECs (Caprio et al.…”
Section: Resultsmentioning
confidence: 99%
“…2008) and that this process contributes to aldosterone‐induced vascular inflammation and atherosclerosis in vivo (McGraw et al. 2013; Marzolla et al. 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest as disease predictors and descriptors are areas of turbulent flow and their effects on the vessel walls. Turbulent flow near the vessel wall has been associated with adverse vascular remodelling, and damage to the vessel wall (3)(4)(5)(6)(7)(8)(9)(10)). …”
Section: Introductionmentioning
confidence: 99%
“…Organ fibrosis and atherosclerosis are promoted by excess aldosterone (10). Upon exposure of vessels to aldosterone in models of atherosclerosis, enhanced placental growth factor (PlGF) expression has been observed, mediated by a mineralocorticoid responsive element in the promoter region of plgf (10,11).…”
Section: Introductionmentioning
confidence: 99%